Use of Metformin and Platelet Reactivity in Diabetic Patients Treated with Dual Antiplatelet Therapy - Verdoia, Monica; Pergolini, Patrizia; Rolla, Roberta; Ceccon, Claudia; Caputo, Marina; Aimaretti, Gianluca; Suryapranata, Harry; De Luca, Giuseppe (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Enhanced platelet reactivity represents one of the major determinants of cardiovascular risk among diabetic patients. The aim of the present study was to evaluate the impact of metformin use on platelet reactivity in diabetic patients receiving dual antiplatelet therapy (DAPT).Methods We included diabetic patients treated with DAPT after an acute coronary syndrome or percutaneous coronary intervention. Platelet reactivity was assessed at 30–90 days by Multiple-electrode aggregometry. In an additional cohort of diabetic patients naïve to antiplatelet therapy, we assessed platelet reactivity by light transmission aggregometry, surface expression of P-selectin and plasma concentration of Thromboxane B2 (TxB2).Results We included 219 diabetic patients, 117 (53.4%) treated with metformin. Metformin was associated with younger age (p=0.03), male gender (p=0.02), lower rate of hypertension (p=0.04), active smoker (p=0.002), previous MI (p<0.001) renal failure (p<0.001), fibrinogen (p<0.001) and C-reactive protein (p=0.04), larger use of diuretics (p=0.04) calcium antagonists (p=0.05), better glycemic control (p<0.001) and higher haemoglobin (p=0.003). The prevalence of HAPR did not significantly differ according to hypoglycemic treatment (p=0.73; adjusted OR[95%CI]=5.63[0.42-76], p=0.19). Moreover, no impact of metformin was observed for HRPR (p=0.77; adjusted OR[95%CI]=1.15[0.55-2.4], p=0.71). Among an additional cohort of 42 diabetic patients naïve to antiplatelet therapy, we confirmed no impact of metformin or insulin on aggregation.Conclusions Our study found no apparent association in diabetic patients treated with DAPT, between the use of metformin and platelet reactivity or the rate of HPR.
Keywords: metformin; platelet reactivity; coronary artery disease